(untitled) (Medical Forum Monthly, 2024)
Objectives: To evaluate the knowledge, attitude and practice of health care staff on bio-safety and biohazards in District Pakpattan. Study Design: Cross Sectional epidemiological Study. Place and Duration of Study: This study was conducted in District Pakpattan Punjab, Pakistan from 1st August 2013 to 30th August 2013. Materials and Methods: The study was carried out to evaluate the knowledge attitude and practice on bio-safety and biohazards of health care providers, who are directly involved in the patient handling e.g. doctors, lady doctor, laboratory and blood bank technicians, Nurses, Dispensers, Lady Health Visitors, Vaccinators ,OT Assistants, dental technicians, dental surgeons, while others were excluded. The target population was 552, and 33% (N=184) population was included in the study as non probability sample to reduce the bias in this reference epidemiological study. A standard questioner was pretested to identify weaknesses and strengths. Respondents interviewed individually and data was analyzed by using SPSS.15.0 for Widows Evaluation Version. Keeping Ethical Consideration in view, formal consent and permission was obtained from concerned Authorities and respondents. Results: The study results on the variables were as; 27(14.6%) had specific training on bio-safety and biohazards,157(85.3%) had no structured training. 96(52%) respondents had habit of eating at work place, laboratory, dressing or examination rooms , 83(45%) don’t have this habits or practice while 6 (3.2%) do this practice sometimes. 98(53%) had habits of storing edibles in the refrigerators meant for vaccines or laboratory purpose, 84(45.6%) don’t have this habits and 2(1.0%) do this practice sometimes. Among females(N=91), 35(38.4%)using cosmetics at work place,42(46%) don’t have this habits or practice,11(12%) do this practice sometimes. 0ut of 161 the 62(40%) had habits of smoking or sniffing at work place, 99(60%) don’t have this habits or practice . 89(48.3%) had habits of cutting nail with teeth and putting pen in the mouth at work, rest 93(50%) don’t have this habits or practice. Conclusion: The study results are consistent and supported by many studies already conducted. Results showing poor knowledge, attitude and poor practices. It demonstrates the serious need of trainings on bio-safety and continuous monitoring on the practices to minimize the health risk, which is a hidden public health problem.